KARAKTERISTIK AIR TANAH DI KECAMATAN TAMANSARI KOTA TASIKMALAYA - Agung Riyadi (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2007)
Pumping test are carried out to determine how much groundwater taken from a well and what effects pumping will have on the aquifer. Theis recovery method aims to find out the aquifer characteristics such as transmisibility and permeability values. This method in principle observes the recovery of ground water surface until stable. This research location at Tamansari distric Tasikmalaya West Java. The value of transmisibilitas and permeabilitas in Tamansari district indicated the groundwater potency is not good for industry ot comercial water. Higher value at Sukahurip and lowest value at Bantarhuni with a permeability coeficient only 1.32 m2/day. Ground water flow (m3/day) between 410 – 4868 m3/day at Mugarsari. Ground water resources is limited potency, especially at dry season, local goverment need to conserv with a build pond or fishpond for reserve water.